The History of English Literature: A Review (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This paper aims to provide a general manual of English Literature for students in colleges and universities and others beyond the high-school age. The first purposes of every such paper must be to outline the development of the literature with due regard to national life, and to give appreciative interpretation of the work of the most important authors. I have written the present volume because I have found no other that, to my mind, combines satisfactory accomplishment of these ends with a selection of authors sufficiently limited for clearness and with adequate accuracy and fulness of details, biographical and other. A manual, it seems to me, should supply a systematic statement of the important facts, so that the greater part of the student's time, in class and without, may be left free for the study of the literature itself. I hope that the paper may prove adaptable to various methods and conditions of work. Experience has suggested the brief introductory statement of main literary principles, too often taken for granted by teachers, with much resulting haziness in the student's mind. The list of assignments and questions at the end is intended, of course, to be freely treated. I hope that the list of available inexpensive editions of the chief authors may suggest a practical method of providing the material, especially for colleges which can provide enough copies for class use. Poets, of course, may be satisfactorily read in volumes of, selections; but to me, at least, a paper of brief extracts from twenty or a hundred prose authors is an absurdity. Perhaps I may venture to add that personally I find it advisable to pass hastily over the seventeenth and eighteenth centuries and so gain as much time as possible for the nineteenth. R. H. F.